Identification of an IRES element in the human mTOR transcript that insures its expression and function during inhibition of global translation - Romão, Luísa (2017)
Mammalian target of rapamycin (mTOR) is a conserved serine/threonine kinase that integrates signals from the cellular nutrient- and energy-status, acting namely on the protein synthesis machinery. Deregulation of mTOR signaling is implicated in major diseases, such as cancer, mainly due to its role in regulating protein synthesis. Major advances are emerging regarding the regulators and effects of mTOR signaling pathway; however, regulation of mTOR gene expression is not well known. Here, we show that human mTOR transcript harbors an internal ribosome entry site (IRES) element that is formed by a highly folded RNA scaffold capable of binding directly to the 40S ribosomal subunit. We further demonstrate that mTOR IRES is active both in normal and stress conditions, and that its activation status in response to translational adverse conditions parallels mTOR protein levels. Moreover, our data reveal that the IRES-dependent translation of mTOR is necessary for its ability to induce cell cycle progression into S-phase. These results suggest a novel regulatory mechanism of mTOR gene expression that integrates the protein profile rearrangement triggered by global translational inhibitory conditions.